Development of intelligent traffic light - Mior Tajul Adzam Selipol Bahari (Universiti Malaysia Perlis, 2008)
Today, most of the traffic lights in Malaysia are controlled by Programmable Logic Control (PLC). This controller is chosen due to its low cost and user friendly programming language. The program could be modified to suit the requirement of any particular traffic lights. This project used the Programmable Logic Controller (PLC) as a controller and it was designed to control the 4-junctions of traffic light. There was 3 mode of operation; Normal mode, Emergency mode and Night mode. In Normal mode, the operation of traffic light have been setting based on the study conducted on the numbers of vehicles move on the road. The traffic light automatically changes to emergency mode operation when there have the emergency vehicle such as police, firebrigade and ambulance use that junction. Third mode is night mode which operate during less traffic are using that junction. The IR transceivers have been used to implement this operation mode.